Modulation of the zebrafish optokinetic reflex by pharmacologic agents targeting GABAA receptors. (3rd April 2018) - Shao, Enhua; Scheetz, Seth D.; Xie, Wenting; Burton, Edward A.
Highlights: We evaluated GABAA -modulating agents in the zebrafish optokinetic reflex (OKR). Picrotoxin decreased reflex gain, and saccade velocity and amplitude. Gaboxadol increased reflex gain, and saccade velocity and amplitude. Quantitative changes were robust and concentration-dependent. The OKR may be useful as a chemical biology and neuropharmacology tool. Abstract: Optokinetic reflex (OKR) responses provide a convenient means to evaluate visual, integrative and oculomotor function in larval zebrafish. We measured multiple aspects of the OKR response in zebrafish exposed systemically to compounds altering signaling at GABAA receptors in order to derive quantitative concentration-response relationships. The GABAA antagonist picrotoxin caused concentration-dependent decreases in reflex gain, saccade velocity, saccade amplitude, interocular concordance and interocular gain. Conversely, the GABAA agonist gaboxadol provoked increases in reflex gain, saccade velocity, saccade amplitude and ocular range at low concentrations, and decreases in some of these parameters at higher concentrations. These data show that GABAA signaling influences multiple aspects of the OKR (including gain, generation of saccades, and coordination between the two eyes) and provide proof of concept that quantitative OKR analysis can be used as a tool for chemical biology and neuropharmacology applications.